Sources for the history of great overseas discoveries and conquists of the New World in the Czech lands and Slovak translations (Theatrum historiae, 2012)
My research stay at the University of Chicago in the ACASA archives was very successful. It brought very valuable results for the Czech and American side: The ACASA Archive currently has a complete collection of the collection. Although the current state of processing of the archive collection is not final, the first and most important step has been taken - the inventory and partial organization of the collection plus a description of the oldest and most historically valuable documents. They map not only the Czech minority in Chicago, but also contain important valuable information about the history of Czech compatriots and the history of Czech immigration to the USA. The sources included in ACASA offer a unique opportunity to gain access to new, as yet unpublished information about Czech-American relations from the mid-19th century to the present.